"The Legacy Will Be the Change": Reconciling How We Live with and Relate to Water - Day, Lindsay; Cunsolo, Ashlee; Castleden, Heather; Sawatzky, Alex; Martin, Debbie; Hart, Catherine; Dewey, Cate; Harper, Sherilee L. (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2020)
Current challenges relating to water governance in Canada are motivating calls for approaches that implement Indigenous and Western knowledge systems together, as well as calls to form equitable partnerships with Indigenous Peoples grounded in respectful Nation-to-Nation relationships. By foregrounding the perspectives of First Nations, Inuit, and Métis peoples, this study explores the nature and dimensions of Indigenous ways of knowing around water and examines what the inclusion of Indigenous voices, lived experience, and knowledge mean for water policy and research. Data were collected during a National Water Gathering that brought together 32 Indigenous and non-Indigenous water experts, researchers, and knowledge holders from across Canada. Data were analyzed thematically through a collaborative podcasting methodology, which also contributed to an audio-documentary podcast (www.WaterDialogues.ca).